PASTORAL KONSELING SEBAGAI PENGURAI SINDROM SARANG KOSONG - Opit, Hesky C; Berdame, Jekson (Institut Agama Kristen Negeri Manado, 2021)
This paper seeks to explore the possibility that empty nest syndrome can be resolved through pastoral counseling services while providing avenues for more in-depth research on this subject. Considering the empty nest syndrome is very rarely raised and used as an object of study by theological academics, especially in the field of pastoral counseling. With regard to the objective, the approach method used is qualitative with an exploratory approach. Through a review of a number of literatures, it is shown that pastoral counseling is able to parse empty nest syndrome because both conceptually and in practice counseling pastoral has an adequate classification.